An inorganic-organic hybrid framework from the assembly of an electron-rich diphosphonate and electron-deficient tripyridyl moiety - Ma, Yu-Juan; Han, Song-De; Pan, Jie; Mu, Ying; Li, Jin-Hua; Wang, Guo-Ming (Journal of materials chemistry. C, Materials for optical and electronic devices, 2018)
The combination of an electron-rich zinc diphosphonate layer and electron-deficient 2,4,6-tri(4-pyridyl)-1,3,5-triazine (TPT) generates a 3D inorganic-organic hybrid with an [-ED-EA-ED-EA-] arrangement (ED = electron donor and EA = electron acceptor), which exhibits a wide and rapid photoresponse upon exposure to the stimulus of sunlight, UV light and X-rays at ambient temperature. Notably, the coloration time is 0.1 s when exposed to UV light (320 nm) generated from a Xe-lamp (150 W). The combination of an electron-rich zinc diphosphonate layer and an electron-deficient tripyridine moiety generates a 3D hybrid framework with excellent photochromism with a wide rapid photoresponse upon exposure to X-rays, UV light and sunlight at ambient temperature.